Digital rubric-based assessment of oral presentation competence with technological resources for preservice teachers - Pérez-Torregrosa, Ana Belén; Gallego-Arrufat, María Jesús; Cebrián-de-la-Serna, Manuel (Universidad de Navarra, 2022)
This study focuses on e-assessment of oral presentation competence using technology resources in a model that combines project-based learning and flipped learning. This study uses a digital rubric to assess oral presentation competence in different situations of progressive assessment for 99 preservice teachers, situations in which participation was either optional or compulsory. Findings show that the digital rubric used at various times is a methodology and a technology that facilitates the feedback process and dialogue between teachers and students about the assessment criteria. The results support future decisions for methodological design of formative assessment appropriate to online learning environments
Keywords: Tecnología educativa; Rubric; Oral presentation competence; Assessment; Preservice teachers